Linear precoder design for non-orthogonal AF MIMO relaying systems based on MMSE criterion - Yunida, Yunida; Nasaruddin, Nasaruddin; Muharar, Rusdha; Away, Yuwaldi (EURASIP journal on wireless communications and networking, 2018)
Multiple-input multiple-output (MIMO) relaying system has attracted the attention of cooperative network researchers, due to its advantage over the conventional single antenna system, in terms of system capacity and spatial diversity. Precoder design is a processing scheme implemented at a source and relay node to improve system performance. We propose a linear precoder design for non-orthogonal amplify-and-forward MIMO relaying systems based on the minimum mean square error (MMSE) criterion. We analyze an upper bound of MMSE using a convenient expression to determine the structure of precoding matrices using the singular-value decomposition technique. Simulation results demonstrate that the proposed precoded scheme outperforms both unprecoded and existing precoded schemes.